Children's comprehension of presuppositions introduced by focus particles: Evidence from Turkish - Topaloğlu, Simge. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
This thesis investigates whether and how Turkish-speaking children interpret the presuppositions of the additive focus particle dA ('also') and the scalar additive focus particle bile ('even'). Experiment 1 examines whether children can utilize prosody to differentiate between two different dA's (i.e., expressing (i) additive focus or (ii) contrastive topic) and whether they can access their different presuppositions and implicatures. The results demonstrate that children over 6 years are competent at doing this, while younger children exhibit a bias towards contrastive readings. Experiment 2 tests the comprehension of dA using OSV sentences, where dA is associated with the object NP. In contrast to Experiment 1, Experiment 2 detects a bias towards additive-focus readings. What children's interpretations seem to have in common in both experiments is a preference for object-focus readings. These results lend further support to the hypothesis that young children may deploy a default strategy to treat object NPs as foci. Experiment 3 investigates the comprehension of bile ('even'). The results show that Turkish children from age 5 onwards are generally good at interpreting bile, though they reach adult-like competence by age 7. Polarity was also found to have a major effect on comprehension. Children were much better at comprehending bile in negative sentences than in affirmative sentences. This disparity between affirmative and negative sentences could potentially be accounted for if the implicatures of bile are pragmatically more robust (i.e., less susceptible to defeasibility) in negative contexts, and an acceptability survey done with adults provides some evidence for this hypothesis
Keywords: Turkish language -- Rhetoric.; Turkish language -- Spoken Turkish.